(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article provides a comprehensive analysis of the problem of psychological preparation for extreme conditions from the perspective of military psychology and the military education system. The factors affecting the psyche of military personnel in extreme situations, as well as stress and adaptation mechanisms, are examined on a scientific and theoretical basis. Modern methods of psychological preparation - psychological training, stress inoculation, simulation and modeling, cognitive-behavioral approaches, and psychophysiological preparation techniques – are systematically presented. The research results allow for the development of practical recommendations for improving psychological preparation for extreme conditions within the military education system.